PELAKSANAAN KURIKULUM 2013 PADA MATA PELAJARAN AL-QURAN HADITS DI MADRASAH IBTIDAIYAH NEGERI 6 KOTA PADANG - Desniwati Desniwati; Aguswan Rasyid; Syaflin Halim (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2022)
The 2013 curriculum that has been in force since 2016 until now has not been fully understood by all educators, so in implementing the curriculum many teachers have difficulty realizing the goals that have been set. Related to this problem, research was conducted to describe the implementation of the 2013 Curriculum, especially the subjects of the Hadith Quran in madrasah Tsanawiyah. Research is conducted without the use of treatment, therefore, the techniques used in collecting data are in the form of observations, interviews and documentation studies. Data collected through established techniques is then analyzed qualitatively, the data analysis process is carried out in a smultan manner, namely starting from data collection, data verification to the conclusion of data analysis. The results of the study are first, the Implementation of the 2013 Curriculum in the subjects of the Qur'anic Hadith has not taken place optimally, this conclusion is based on the reality that starting from the planning process to the evaluation there are inconsistencies and inconsistencies between all aspects. Second, the problem in the implementation of the 2013 curriculum in the subjects of the Qur'anic Hadith is in the aspects of methods, media and evaluation of learning. Third, the step that can be done to minimize the problem is to maximize training activities that can improve the ability of teachers to carry out the 2013 curriculum.